Birth Doula Care in California During COVID-19: The Impacts of Social Distancing on a High-Touch Helping Profession. (August 2022) - Lisenbee, Jodie; Gil-Rivas, Virginia; Webb, Jennifer B.; Dahl, Alicia A.; Quinlan, Margaret M.
Birth doulas were deemed "non-essential" personnel during the COVID-19 pandemic and were generally excluded from attending hospital births in person. This study documents the impacts of pandemic-related contextual factors on birth doula care in the San Francisco Bay Area, examines how doulas adapted their services, and explores implications for policy and practice. We employed a contextually bound qualitative case study methodology driven by social action theory and conducted interviews with 15 birth doulas. The pandemic disrupted physical settings, the social environment, communication modalities, contractual arrangements, and organizational level factors. The historical context also amplified awareness of institutionalized racism in birth settings and highlighted birth doulas' advocacy role. Striking deficits exist in birth doulas' integration into US healthcare systems; this made their services uniquely vulnerable to the pandemic circumstances. Birth doulas' value ought to be more formally recognized within health policy, health insurance, and hospital systems as complementary care to that provided by medical providers to improve access to high-quality perinatal care.